PENGEMBANGAN BUKU CEKAWAN (CERITA PUNOKAWAN) UNTUK SISWA SEKOLAH DASAR - Nova Sulistiani, Fana; Widiastuti, Sripit; Fauzi, Adin (Penerbit Widina, Widina Media Utama, 2022)
The teaching and learning process that takes place makes students easily bored and tend not to be interested in learning using the Javanese Gegladhen Book or hearing Punokawan stories from teachers, because they cannot read and see directly the description of the Punokawan storyline, thus causing the non-achievement of learning objectives. Based on the background that has been found, the formulation of the problem can be obtained as follows: How is the feasibility of learning resources. CEKAWAN Book (Punokawan Stories) for Elementary School Students? How do teachers and students read the learning resources of the CEKAWAN Book (Punokawan Story) for Elementary School Students? This research approach includes Research and Development (RD) research. According to (Sugiyono, 2016), Research and Development (RD) is a research method used to produce a particular product and test the effectiveness of the product. This research aims to produce or develop products. The product developed in this study is a learning resource in the form of a CEKAWAN Book (Punokawan Story) for Elementary School Students.This research refers to the research and development design of modifications of the development model according to Borg and Gall. The result of the research and development of the resulting product is the cekawan (Punokawan Story) book for elementary school students. The results of the validation of the feasibility of assessment learning resources from 6 validators, Material experts 78.66%, Linguists 82.22%, and media experts 77.33% categorized as